A Postcolonial Biography of Sadrach: the Tragic Story of an Indigenous Missionary - Singgih, Emanuel Gerrit (Al-Jamiah Research Centre, 2015)
Nowadays, many Indonesian Christians are fully aware that evangelic mission in Indonesian context is to be involved in the dialogue of life with oneâs neighbor and share their struggles. Sadrach, an indigenous missionary who lived in 19th century, can be seen as a pioneer in this mission method. However, this method was not accepted by the foreign missionaries at that time. They accused Sadrachâs method as a form of syncretism. This work is an attempt to analyze Sadrachâs biography in the framework of postcolonial theory which argues that Indonesian Christians have to learn about their colonial past and strive to maintain equal relationships with non-Indonesian Christians. It is hoped that his achievements can be appreciated by the present generation, and they will not repeat the mistakes of the past. It is also good to be aware that resistance to Sadrachâs mission nowadays will come from some contemporary international mission-bodies which continue the old way of propagating Christian faith without regard to the context of Indonesia.[Banyak orang Kristen sekarang ini sadar bahwa misi dalam konteks Indonesia adalah melibatkan diri dalam dialog kehidupan dengan sesama dan ambil bagian dalam pergumulannya. Sadrach, seorang penginjil lokal yang hidup pada abad ke-19 dapat dianggap sebagai salah satu pelopor metode misionaris seperti ini. Akan tetapi penyebaran misi ala Sadrach ini tidak diterima oleh para misionaris asing. Upaya seperti ini dianggap sebagai sinkretisme. Tulisan ini merupakan studi biografi Sadrach dalam kerangka teori poskolonial yang bertujuan untuk menunjukkan peranan Sadrach dalam penyebaran misi Injil di Indonesia. Diharapkan generasi sekarang akan belajar dari dan tidak mengulangi kesalahan-kesalahan masa lampau. Studi ini juga untuk menyadarkan bahwa perlawanan terhadap model misi Sadrach pada masa kini akan muncul dari badan-badan misi internasional yang tetap menjadi model-model misi Kristen yang tidak memedulikan konteks Indonesia sama sekali.]